Analysis of nutritional status of toddlers in health centers in the Banda Aceh Region, Indonesia - Namira Yusuf (Science Midwifery, 2023)
This study addresses a highly relevant objective by comprehensively examining the nutritional status of toddlers in the Banda Aceh region, Indonesia. Focusing on stunting, undernutrition, and malnutrition, the research employs an analytical descriptive method to precisely depict the toddlers' health. The study was conducted across 11 health centers in Banda Aceh from March 21st to June. Primary and secondary data were collected for analysis. Primary data involved field surveys with toddlers, while secondary data included literature analysis and document review. The findings unveil detailed insights into toddler nutrition across Banda Aceh's health centers. Stunting prevalence varies significantly, with Meuraxa center having the highest at 17.54% and Baiturrahman center the lowest at 3.30%. Undernutrition rates differ too, ranging from 2.63% to 11.37%. Although undernutrition is generally low, focusing on even relatively low cases is crucial due to potential impact on toddler growth. Malnutrition cases are also relatively limited but require attention, given their potential effects on toddler development and health. These findings emphasize the need for targeted interventions and strategies to address varying nutritional challenges among toddlers in the Banda Aceh region. The research contributes valuable insights for healthcare policymakers and practitioners to enhance child health and well-being in the area.